Diagnostic and therapeutic pathways of lip lesions in onco hematology: report of a challenging pediatric case - Boechat Feyo, Victória; Roeles, Iasminy Soares de Oliveira; Fabri, Júlia Campos; Provinciali, Lydia Silva; Esteves, Tereza Cristina; Chaves, Maria das Graças Afonso Miranda; Fabri, Gisele Maria Campos (Brazilian Dental Science, 2024)
Background: Oncohematologic patients have a high incidence of thrombosis, due to either their the underlying disease or treatment. The standard management involves low molecular weight anticoagulants; however, these agents may increase bleeding risk. Case report: A rare case of acute hemorrhagic lesion in pediatric patient is described, emphasizing the diagnostic challenges encountered. An eight-year-old male with severe anemia, fever, and thrombosis of the superior and inferior vena cava was admitted for diagnostic evaluation. Enoxaparin was prescribed, and the diagnosis of anaplastic large cell lymphoma (ALCL) was confirmed. After 20 days of anticoagulant therapy, the patient developed epistaxis followed by the formation of oral hemorrhagic edema in the upper and lower lips. A specific protocol of oral care with multiprofessional team was implemented.The lesion showed resolution, along with physical and emotional recovery. Conclusion: The personalized care protocol successfully restored essential oral functions, including chewing, swallowing, digestion, taste, and speech, thereby redefining the true significance of a smile; crucial in oncohematological patients.KEYWORDSDentistry; Oncology; Oral cavity; Pediatrics; Thrombosis.